1992
DOI: 10.1152/ajpendo.1992.263.4.e794
|View full text |Cite
|
Sign up to set email alerts
|

Meal stimulation of albumin synthesis: a significant contributor to whole body protein synthesis in humans

Abstract: The present studies were performed to test the hypothesis that the liver, by increasing the synthesis of specific plasma proteins during the absorption of an amino acid meal, may play an important role in the temporary "storage" of ingested essential amino acids and to explore the effects of glucocorticosteroids and recombinant human growth hormone (rhGH) on these processes. The fractional synthetic rates of albumin and fibrinogen were determined using simultaneous infusions of intravenous [1-14C]leucine and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
2
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(134 citation statements)
references
References 14 publications
14
116
2
1
Order By: Relevance
“…Our forearm catheterization data agree with one of these studies (6) as regards meal-induced acute stimulation of forearm protein synthesis. They agree also with previous findings obtained at the whole body level, as regards the simultaneous inhibition of endogenous proteolysis and the stimulation of protein synthesis after a mixed meal (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our forearm catheterization data agree with one of these studies (6) as regards meal-induced acute stimulation of forearm protein synthesis. They agree also with previous findings obtained at the whole body level, as regards the simultaneous inhibition of endogenous proteolysis and the stimulation of protein synthesis after a mixed meal (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies in humans have shown that meal ingestion is accompanied by both an increase of whole body protein synthesis and a suppression of protein degradation (3)(4)(5)(6)(7)(8)(9)(10)(11). However, the response to meal of protein kinetics in individual human body tissues is far less known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulated synthesis of ApoB 100 suggests very low density lipoprotein secretion induced in response to an increased energy requirement of muscle and heart for very low density lipoprotein-bound TG. However, the synthesis of albumin, the most abundant plasma protein, is regulated by amino acid substrate availability in normal conditions (46). Although it is not clear why fasting reduces fibrinogen synthesis, a similar reduction in fibrinogen synthesis was observed in healthy human subjects after a short term increase in plasma free fatty acids by lipid infusion (47).…”
Section: Plasma Proteome Dynamicsmentioning
confidence: 93%
“…Serum concentration of albumin is determined by its synthesis, breakdown, losses, volume of distribution and exchange between intra-and extravascular spaces (Klein, 1990;Jeejeebhoy, 1998). Nutritional supplementation has been shown to optimize anabolic activity of the liver to synthesize albumin in healthy subjects, possibly owing to increases in circulating insulin, which positively modulates albumin FSR (De Feo et al, 1992). Exercise is a potential treatment for wasting syndromes as it directs more nutrients toward muscle tissues and induces a greater sensitivity and responsiveness to metabolic events regulated by insulin compared with nutrient administration alone (Wasserman et al, 1991).…”
Section: Discussionmentioning
confidence: 99%